HUBUNGAN PENGETAHUAN DENGAN PERSEPSI REMAJA TENTANG SEKS PRANIKAH DI SMKN 3 KOTA BENGKULU - ruri maiseptya sari (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2019)
ABSTRACT Sexual behavior is all behavior driven by sexual desire, both with the opposite sex and same-sex. This study aims to determine the relationship of knowledge with adolescent perceptions about premarital sex at SMK 3 Kota Bengkulu. This study uses an analytical design, with a cross sectional approach. The population in this study was 305 students. The sampling technique in this study using Proportional Random Sampling obtained a sample of 75 students. Data collection techniques in this study use primary data and secondary data. The results obtained: (1) there were 18 students (24%) had insufficient knowledge, 31 students (41,3%) had sufficient knowledge, 26 students (34,7%) had good knowledge about premarital sex. (2) there were 43 students (57,3%) had negative perceptions and 32 students (42,7%) had a positive perception about premarital sex. (4) there was a relationship between knowledge of premarital sex in class XI students at SMK 3 Kota Bengkulu with medium category. (5) there is a relationship between perceptions of premarital sex in class XI students in SMK 3 Kota Bengkulu in the moderate category. It is expected that students can find out about sexuality in adolescents so that students are able to provide appropriate information to students of SMKN if doing research and counseling. Keywords: Premarital Sex, Knowledge, Perception.